2016
DOI: 10.1111/bjh.14326
|View full text |Cite
|
Sign up to set email alerts
|

Autologous stem cell‐based therapy for sickle cell leg ulcer: a pilot study

Abstract: Recurrent chronic leg ulcers are among the most severe vasculopathic complications of sickle cell disease (SCD). Their treatment remains a challenge. Stem cell therapy with bone marrow mononuclear cells (BMMC) is a promising new therapeutic option for other forms of chronic ulcers. This prospective pilot study was performed to evaluate safety and feasibility of BMMC implantation in patients with SCD and chronic leg ulcers (SCLU). Ulcer closure, recurrence and local pain were evaluated. BMMC were successfully a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 19 publications
1
12
0
1
Order By: Relevance
“…In these mice, we confirmed that skin healing was delayed due to a reduced migration of marrow endothelial progenitor cells in wounds in relation with a defect in skin SDF1 production . In accordance with our study, another group has shown that autologous marrow progenitors injected into patient's ulcers were able to allow significant healing of ulcers . Therefore, local cutaneous as well as distant – mainly marrow‐occurring mechanisms related to wound angiogenesis – appear altered in affected patients.…”
supporting
confidence: 89%
“…In these mice, we confirmed that skin healing was delayed due to a reduced migration of marrow endothelial progenitor cells in wounds in relation with a defect in skin SDF1 production . In accordance with our study, another group has shown that autologous marrow progenitors injected into patient's ulcers were able to allow significant healing of ulcers . Therefore, local cutaneous as well as distant – mainly marrow‐occurring mechanisms related to wound angiogenesis – appear altered in affected patients.…”
supporting
confidence: 89%
“…A pilot study in 2016 used cellular therapy: stem cells from bone marrow mononuclear cells (BMMC) were injected locally in 23 patients with SCLUs. 63 During the 6-month follow-up period, 29.2% of the ulcers treated achieved total healing, which does not appear different from results obtained using standard wound care. The rationale behind using these autologous cells was that progenitor stem cells (CD34CD45low and fibroblast colony-forming units) in BMMC were found to be significantly reduced in SCLU patients when compared with SCD patients without ulcers.…”
Section: Cell-based Therapymentioning
confidence: 60%
“…Plaquetas, linfócitos 22 Ortopedia A terapia com células tronco mesenquimais vem se tornando um procedimento clínico muito aplicado no tratamento de patologias relacionadas com a cartilagem e com o menisco, incluindo a osteoartrite. 23 Corroborando com isso, o Dr. Roberto Dórea e o Prof. Ricardo Ribeiro dos Santos, fizeram um trabalho que usou o Plasma rico em fatores de crescimento e células mesenquimais para tratar degeneração condral grau IV na articulação do joelho.…”
Section: Tgf-β1unclassified